Nephrotic syndrome associated with hepatointestinal schistosomiasis Síndrome nefrótica associada à esquistossomose hepatointestinal - H. Abensur; I. Nussenzveig; L.B. Saldanha; M.S.C. Petalozzi; M.T. Barros; M. Marcondes; R.T. Barros (Revista do Instituto de Medicina Tropical de São Paulo, 1992)
Schistosomal nephropathy has long been related to the hepatosplenic form of schistosomiasis. In the last few years, 24 patients with hepatointestinal schistosomiasis and the nephrotic syndrome were studied. Aiming at evaluating a possible etiologic participation of schistosomiasis in the development of the nephropathy, this group was comparatively studied with a group of 37 patients with idiopathic nephrotic syndrome. Both groups had a different distribution of the histologic lesions. In the group with schistosomiasis there was a statistically significant prevalence of proliferative mesangial glomerulonephritis (33.3%), whereas in the control group there was prevalence of membranous glomerulonephritis (32.4%). On immunofluorescence, IgM was positive in 94.4% of the patients with schistosomiasis versus 55.0% in the control group (p<0.01). In the group with schistosomiasis, 8 patients evidenced mesangial proliferative glomerulonephritis and 5, membra-noproliferative glomerulonephritis. In both histological types immunofluorescence showed IgM and C3 granular deposits in the glomeruli. The data in this study suggests that mesangial proliferative and membranoproliferative glomerulonephritis, with glomerular granular IgM and C3 deposits, represent the renal lesions of the schistosomiasis associated nephropathy. A nefropatia esquistossomótica está classicamente vinculada à fornia hepatoesplênica da esquistossomose. Ao longo dos últimos anos 24 casos de pacientes esquistossomóticos hepato-intestinais e portadores de síndrome nefrótica foram estudados. Com o objetivo de verificar a possível participação etiológica da esquistossomose na gênese da nefropatia, analisamos este grupo comparativamente ao grupo de 37 doentes portadores de síndrome nefrótica idiopática. Ambos os grupos apresentaram distribuição distinta dos tipos histológicos de glomerulopatia. No grupo de esquistossomóticos houve predomínio estatisticamente significante de glomerulonefrite proliferativa mesangial (33.3%), enquanto no grupo controle houve ...